Progressive Visual Secret Sharing Scheme for QR Code Message - Patil, Komal S; Bhagate, Suhas B (International Journal of Computer Sciences and Engineering, 2019)
The quick response (QR) code was designed for storage information and high speed reading applications. With the wide application of QR code, the security problem of QR code is serious, such as information leakage and data tampering. The QR code contains secret message. In order to solve the QR information security problem, this paper proposed progressive visual secret sharing schemes for QR code message. In progressive visual secret sharing scheme the QR code message is divided into several parts called shares, which separately reveals no knowledge about the QR code message. QR code message can be revealed progressively by more and more shares one another. It improves the security of the data transmission and also improves the clarity of a secret image step by step.